Improving Student Learning Outcomes in Suggestion Sentence Material with Learning Video Media for Class III Semester I SD Negeri Luwunggede 04 - Laeli Musyarofah (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in Indonesian language subject matter in grade III elementary schools using instructional video media. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle having one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Data collection techniques are observation and tests. Based on the data analysis, it was found that the use of instructional video media in Indonesian language subject matter content in suggestion sentences could improve student learning outcomes as indicated by the level of learning completeness in the initial conditions 40% to 60% in cycle I , and increased to 90% in cycle II. The final conclusion from the implementation of this classroom action research is that the use of instructional video media is able to improve student learning outcomes on Indonesian language subject matter content in the suggestion sentence material at SD Negeri Luwunggede 04, Larangan District, Brebes Regency.